Evaluating the qualities of probiotic products by a DGGE-based procedure - Hanh, Tran My; Thi Dung, Cao; Thi Thanh Huyen, Tran; The Hai, Pham (Vietnam Journal of Biotechnology, 2020)
The quality of the probiotics is determined by the microbiological composition and can thus be verified by analyzing this characteristic. The use of the Denaturing Gradient Gel Electrophoresis (DGGE) allows the detection of each microorganism through the corresponding band on the gel, which can be considered as the "bar code" of that microorganism. This "bar code” principle demonstrates the potential for the application of DGGE technology to test microbial probiotics with or without a bacterium as registered to assess whether they are qualified. As such, in this study, we experiment the application of DGGE method to test 10 commercial probiotic products, with a focus on products consisting of only bacteria which dominate the market. First, we performed DNA genome extraction and amplification of 550 bp DNA of the 16S rDNA by PCR. Then, the  amplicon was analysed on polyacrylamide gels containing a 30% to 60% linear denaturing gradient of urea and formamide. Microbial composition of 7 of the 10 products showed a strong correlation between DGGE results with product labeling as well as isolation of micoorganism. This study thus demonstrates the potential application of DGGE technology in evaluating the qualities of probiotic products.